Siak Sri Indrapura Sultanate: Role in Shipping and Trade in the Malacca Strait in the 18th Century - Hasudungan, Anju Nofarof; Sunarti, Linda (Program Studi Pendidikan Sejarah FKIP Universitas Mulawarman, 2024)
The purpose of this study was to examine the role of the Siak Sri Indrapura Sultanate in shipping and trade in the Melaka (Malacca) Strait in the XVIII century. By using the historical method of literature study approach, there is evidence of the triumph of the Siak Sri Indrapura sultanate in the Malacca Strait. The Siak Sultanate in 1767 under the rule of King Ismail showed its dominance in the territorial waters of East Sumatra by controlling the Tin trade on Bangka Island. The expansion of Siak influence during the reign of King Ismail continued to grow significantly starting from Terengganu, Jambi, and Palembang. In 1780 Siak's territory they reached the Langkat, Deli, and Serdang areas. The Siak Sri Indrapura Sultanate took advantage of the control of trade through the Straits of Malacca. This success was also supported by the ability of the Sultanate of Siak to control the pirates in the area. Search results from Dutch records recorded that in 1783 there were 171 merchant ships from Siak to Malacca. The position of Siak can be said to be a triangular area of trade between the Dutch in Malacca and the British on the island of Pinang. At that time, the Siak River was an area where various trade products were collected, ranging from camphor, tin, and gold. Even the people of Siak are active in the timber industry, especially for shipbuilding and other construction.